Sistem Pendukung Keputusan Berbasis Pocket Pc Sebagai Penentu Status Gizi Menggunakan Metode Knn (K-Nearest Neighbor) - Tedy Rismawan; Ardhitya Wiedha Irawan; Wahyu Prabowo; Sri Kusumadewi (Faculty of Industrial Technology Universitas Islam Indonesia, 2008)
The nutrition problem is very important problem that need more attention. If someone doesn’t know about his nutrition status, he can’t control how much nutrition value should be needed by his body. In this research, it has been built a Decision Support System (DSS) to compute nutrition status. The system needs physical condition from user via user interface. Pocket PC platform used to develop this DSS. The computation of nutrition status based on K-Nearest Neighbor (K-NN). The K-NN method will look for the shortest distance between evaluated data and K nearest data in the data training set The result of this research shows that this system can help user to get information about his nutrition status, so he can keep his nutrition normal status to avoid he diseases attack. Keywords: Decision Support System, nutrition status, KNN(K-Nearest Neighbor), Pocket PC